Influence of different versions of the straight forward punch on the obtained force, energy and power - measurements of taekwon-do ITF athletes` performance - Wasik, J.; Nowak, K. (Archives of Budo Conference Proceedings, 2015)
Background and Study Aim. The aim of the study was the knowledge about the values of force, energy and power obtained during performance of the straight punch in two different techniques. Material and Methods. 15 taekwon-do ITF (International Taekwon-do Federation) athletes were asked to participate in the study. They were asked to perform the traditional and sports version of the punch three times each. The research was carried out with the use of Smart-D system manufactured by Italian BTS Spa company and used for complex analysis of movements. Results. The research shows that the average delivery time of 0.170 ± 0.007 s of the sports version punch is significantly shorter than that of its traditional version whose average is 1.060 ± 0.142 s (p<0.01). The kinetic energy of 2299 ± 320 J and force of 3284 ± 555 N were obtained in the traditional technique of the punch. The force of this strike is comparable to the force obtained in the roundhouse kick. The other technique (i.e. the sports one) obtained only 916 ± 60 J and 1308 ± 173 N (p<0.01). Thus, a greater force and a greater energy were obtained in the traditional technique. However, the calculated power of 5630 ± 247 W is considerably higher for the sports technique of the strike, which signifies a high pace of energy production (the traditional strike achieved only 2598 ± 283 W). Conclusions. Having analyzed the obtained results it can be stated that the aim of a strike determines the way the strike is delivered. The traditional taekwon-do punch is used to perform mechanical work and produce a maximum kinetic energy, which is necessary for breaking, whereas the sports punch requires a short time of delivery, which gives great power, i.e. high rate of energy production. That is the reason why it is used in combat.